Sex differences in concentrations of HMGB1 and numbers of pigmented monocytes in infants and young children with malaria. (October 2021) - Kanoi, Bernard N.; Egwang, Thomas G.
Abstract: Sex remains a key biological variable affecting human innate and adaptive immune responses to infection and in pathogenesis of diseases. In malaria, females demonstrate higher concentrations of antibodies and rates of severe adverse events and mortality following malaria vaccination. Although monocytes/macrophages play a crucial role in disease and protection in malaria, no studies have investigated sex differences in their functions in production of proinflammatory cytokines and chemokines in malaria-infected subjects. Here, we show significant sex differences in serum concentrations of HMGB1, a non-histone chromatin-associated protein, and numbers of pigmented monocytes, which are both markers of severe malaria, in infants and young children <5 years old from a malaria endemic region in Northern Uganda. Female infants and young children with clinical malaria had significantly higher HMGB1 concentrations than males, and female infants and young children with asymptomatic malaria had significantly lower numbers of pigmented monocytes than males with asymptomatic malaria. There was (1) a significant correlation between HMGB1 concentrations and pigmented monocyte numbers in female but not male infants; and (2) a significant correlation between HMGB1 concentrations and parasite densities in female but not male infants. These findings suggest that female infants and young children with clinical malaria might be at a greater risk of morbidity characterized by higher serum HMGB1 levels.